Multisite Reproducibility of Results Obtained by the Broth Microdilution Method for Susceptibility Testing of Mycobacterium abscessus, Mycobacterium chelonae, and Mycobacterium fortuitum - Woods, Gail L. (American Society for Microbiology, 1999)
A multicenter study was conducted to assess the interlaboratory reproducibility of broth microdilution testing of the more common rapidly growing pathogenic mycobacteria. Ten isolates (four Mycobacterium fortuitum group, three Mycobacterium abscessus, and three Mycobacterium chelonae isolates) were tested against amikacin, cefoxitin, ciprofloxacin, clarithromycin, doxycycline, imipenem, sulfamethoxazole, and tobramycin (M. chelonae only) in four laboratories. At each site, isolates were tested three times on each of three separate days (nine testing events per isolate) with a common lot of microdilution trays. Agreement among MICs (i.e., mode ± 1 twofold dilution) varied considerably for the different drug-isolate combinations and overall was best for cefoxitin (91.7 and 97.2% for one isolate each and 100% for all others), followed by doxycycline, amikacin, and ciprofloxacin. Agreement based on the interpretive category, using currently suggested breakpoints, also varied and overall was best for doxycycline (97.2% for one isolate and 100% for the rest), followed by ciprofloxacin and clarithromycin. Reproducibility among MICs and agreement by interpretive category was most variable for imipenem. Based on results reported from the individual sites, it appears that inexperience contributed significantly to the wide range of MICs of several drugs, especially clarithromycin, ciprofloxacin, and sulfamethoxazole. New interpretive guidelines are presented for the testing of M. fortuitum against clarithromycin; M. abscessus and M. chelonae against the aminoglycosides; and all three species against cefoxitin, doxycycline, and imipenem.